Building structural work for concrete slab & column / Umairah Fuad - Fuad, Umairah (Universiti Teknologi MARA UiTM,Perak, 2022)
Building structure is very important thing in constructing the building, therefore this report will discuss about the method to develop concrete slab and column. This report was conducted for single storey bungalow house at Jitra, Kedah. The objective of this report is to analyze the proper technique and materials used for constructing concrete slab and columns in order to avoid structural flaws. Particularly, it analyzes whether there is another issue that occurred influenced the building's structural failure. To test the hypothesis that lesser issues lead to a higher rigidity of the building structure, an observation was conducted throughout a visit at construction site. The observation was carried out along with an interview with sub-contractor on the construction site were undertaken. Sub-contractors were asked about every step in developing concrete slab and columns, as well as some construction precautions for preventing the structure collapsing. The data supported the hypothesis that higher rigidity of the building structure is related with fewer issues. This report concludes that when a problem arises during the pre - construction stage, cracking and collapsing of the structure are more likely to occur. The use of the incorrect material also one of the reasons for building’s failure. In fact, the right procedure and material needed should be taken into the account when constructing the building structure.